Ein neuer Idoltyp aus Siidosteuropa - Boroffka, Nikolaus (Arheološki vestnik, 1993)
Two idols from the site of Livezile "La Izvoru Popii", judet Alba in Romania are analysed. They are made from the frontal part of a lower jaw (mandibula) with forward incisors (incisivi 1 right and 1 left) of a domestic pig (Sus scrofa domesticus). They are polished and perforated near the top. Thus, the perforations represent eyes and the incisors feet. This type of idol is so far unknown in the literature. It is concluded on the basis of the accompanying finds and the small number of analogies that the two idols belong to the end of the Copper Age or the beginning of the Early Bronze Age. They probably served as pendants or amulets, as is suggested by the holes. However, it is not clear whether or not they can be linked with burial ritual.